Whole paternal uniparental disomy of chromosome 4 with a novel homozygous IDUA splicing variant, c.159‐9T>A, in a Chinese patient with mucopolysaccharidosis type I - Lulu Yan; Shuxia Ding; Yan He; Bin Fu; Changshui Chen; Haibo Li (Molecular Genetics & Genomic Medicine)
Abstract Background Mucopolysaccharidosis type I (MPS‐I) is a rare autosomal recessive genetic lysosomal storage disorder that is caused by pathogenic variants of the α‐L‐iduronidase (IDUA) gene. This study aimed to identify the genetic causes of MPS‐I in a Chinese patient and construct a minigene of IDUA to analyze its variants upon splicing. Methods Whole‐exome sequencing (WES) and Sanger sequencing were used to confirm the potential causative variants. Single‐nucleotide polymorphism (SNP) array was subsequently performed to confirm uniparental disomy (UPD). Minigene assay was performed to analyze the effect on splicing of mRNA. We meanwhile explored the conservative analysis and protein homology simulation. Results A novel homozygous splicing mutation of IDUA, c.159‐9T>A, was identified in an individual presenting with overlapping features of MPS‐I. Interestingly, only the father and sisters, but not the mother, carried the variant in a heterozygous state. WES and SNP array analyses validated paternal UPD on chromosome 4. Minigene splicing revealed two aberrant splicing events: exon 2 skipping and intron 1 retention. Moreover, the specific structure of the mutant protein obviously changed according to the results of the homologous model. Conclusions This study describes a rare autosomal recessive disorder with paternal UPD of chromosome 4 leading to the homozygosity of the IDUA splicing variant in patients with MPS‐I for the first time. This study expands the variant spectrum of IDUA and provides insights into the splicing system, facilitating its enhanced diagnosis and treatment.